Understanding the plant-pathogen interactions in the context of proteomics-generated apoplastic proteins inventory - Gupta, Ravi; Lee, So Eui; Agrawal, Ganesh K.; Rakwal, Randeep; Park, Sangryeol; Wang, Yiming; Kim, Sun T. (Frontiers in Plant Science, 2015)
The extracellular space between cell wall and plasma membrane acts as the first battle field between plants and pathogens. Bacteria, fungi, and oomycetes that colonize the living plant tissues are encased in this narrow region in the initial step of infection. Therefore, the apoplastic region is believed to be an interface which mediates the first crosstalk between host and pathogen. The secreted proteins and other metabolites, derived from both host and pathogen, interact in this apoplastic region and govern the final relationship between them. Hence, investigation of protein secretion and apoplastic interaction could provide a better understanding of plant-microbe interaction. Here, we are briefly discussing the methods available for the isolation and normalization of the apoplastic proteins, as well as the current state of secretome studies focused on the in-planta interaction between the host and the pathogen.